Empowering sustainable development: revolutionizing agricultural green total factor productivity through rural digitalization - Zeng, Fanjun; Zhou, Yingying; Wei, Bin (Frontiers in Sustainable Food Systems, 2024)
The rapid advancement of digital technology has catalyzed the emergence of “digital villages,” presenting both new opportunities and challenges for the digital transformation of agriculture. This transformation has become a core driving force behind sustainable agricultural development. This paper explores the impact of digital rural development on agricultural green total factor productivity and its underlying mechanisms, aiming to provide fresh empirical insights for high-quality agricultural development. To conduct this research, the study analyzes data from 30 provincial-level administrative regions of mainland China (excluding Tibet) from 2011 to 2020 using a two-way fixed effects model. The findings reveal that: (1) Rural digitalization significantly enhances agricultural green total factor productivity. This finding holds after province-year clustering robust standard error estimates, winsorization analyses, and excluding years affected by the COVID-19 pandemic. (2) The underlying mechanisms can be understood through the lenses of digital financial inclusion and the integrated development of primary, secondary, and tertiary industries. (3) Heterogeneity tests show that the positive impact is more pronounced in regions with higher informatization levels and central regions of China. Fundamentally, this study aims to elucidate China's efficacy in rural digitalization and the green transformation of agriculture to an international audience. It seeks to provide insights and guidance on formulating more scientific, efficient, and sustainable strategies for agricultural development worldwide, thereby promoting green agricultural growth and supporting rural revitalization.